Mental retardation - Beirne-Smith, Mary.; Ittenbach, Richard; Patton, James R. (New York : Merrill, 1994)
Focuse's on the unique relationship between the special educator and the learner with retardation. Offers a comprehensive, introduction to the field, from history and background, to the day-to-day problems of citizens with retardation and their place in society.
Includes bibliographical references and indexes.
Keywords: Intellectual Disability; Education of Intellectually Disabled